First regionalized social accounting matrix for Egypt: A 2015 nexus project social accounting matrix - Randriamamonjy, Josee; Raouf, Mariam; Thurlow, James; Central Agency for Public Mobilization and Statistics (International Food Policy Research Institute, 2019)
The Central Agency for Public Mobilization and Statistics (CAPMAS) is pleased to present the first regionalized social accounting matrix (SAM) for Egypt. This SAM marks a major milestone in “localizing” development research and policy in Egypt and is expected to be most valuable for the development, implementation, and assessment of Egypt’s national and local development plans, like Egypt’s Sustainable Development Strategy 2030. In addition to standard SAMs, which combine many national datasets from institutions such as Central Banks, Ministries of Finance and Agriculture, and Statistical Bureaus, this regionalized SAM makes extensive use of sub-national level information such as the Economic Survey and Household Income and Expenditure Survey (HIECS) produced by CAPMAS, regional GDP estimates by the Ministry of Planning, Monitoring and Administrative Reform, and the Agricultural Bulletins with information at the Governorate level produced by the Ministry of Agriculture and Land Reclamation. With this data it becomes possible to provide a detailed, socioeconomic status update for different regions within Egypt. As such, the disaggregated SAM allows for analyzing developmental issues at regional level and to better understand the potential impacts of policy changes at the local level.